Analysis of Raw Materials Bokar Procurement Planning to Produce Pallet at PT Perkebunan Nusantara V Bukit Selasih, Kabupaten Indragiri Hulu, Riau - Marpaung, Rio Jones Martahan (Jurnal Aplikasi Manajemen, 2015)
The aim of this study is to determine how much raw material requirements neededin the future, by using several methods of forecasting time series model (time series), whichwill be selected as the most effective method for forecasting the need for raw materials. Inaddition, this study also discusses the factors that influence the procurement of raw materialsto the PT. Perkebunan Nusantara V Bukit Selasih. The data were obtained by directobservation keperusahaan as the research object, there is, PT Perkebunan nusantara VBukit Selasih and interviews with the parties of the company, leaders, and some of theworkers.Based on the results of the research method of time series model (time series) wasperformed least squares trend and the moment trend. The prediction in using the forecastingleast squares trend results do not correspond to the reality. This is because the value of MADon the method of least squares trend is still too large when compared to the moment trendmethod.It was concluded that the right forecasting method to predict the need for bokar rawmaterials at. PT Perkebunan Nusantara V Bukit Selasih is least squares trend and momenttrend because based on the both calculation showed the same results of forecasting andvalues. However, in this study, in order to predict the raw materials in the year 2014-2020used forecast moment trend method.